"Nisem 0815 Korošec ---" - primeri etnične identifikacije pri slovensko govorečih (post)adolescentih na dvojezičnem avstrijskem Koroškem - Vavti, Štefka (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2009)
Problems of ethnic identification - young Slovenes at Southern Carinthia (Austria). The demographic and socioeconomic data show, that the young generations of small ethnic groups like the Slovenes in Southern Carinthia (Austria) are threatened: Through processes of globalization and individualization the younger generation has to redefine its identification. Furthermore, demographic and socio-economic processes like declining birth rates, intermarriage and migration threaten the (ethnic) future of these young Slovenes: In this generation, for instance, the communication value of autochthonous languages has been in a permanent decline (e.g. English as lingua franca in internet and science). In this article I will present the qualitative, biographic approach of my research work: On the basis of selected examples I will demonstrate, how young Slovenes in Southern Carinthia identify and locate themselves in their respective ethnic group. Whereas young people who are well integrated in Slovene schools, families and cultural organizations still feel deeply rooted in their ethnic group, those living in ethnic mixed families or in German speaking environments with biographical breaks and lack of Slovene political/cultural membership, often show distance,ambivalence and various affiliation-conflicts, but with a feeling of belonging to their Slovene ethnic roots.
Keywords: Austria; Avstrija; Koroška; narodne manjšine; zamejski Slovenci; mladi; narodna identiteta